2021
DOI: 10.12688/wellcomeopenres.15387.3
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and internal validation of a data-driven prediction model to guide frontline health workers in triaging children under-five in Nairobi, Kenya

Abstract: Background: Many hospitalized children in developing countries die from infectious diseases. Early recognition of those who are critically ill coupled with timely treatment can prevent many deaths. A data-driven, electronic triage system to assist frontline health workers in categorizing illness severity is lacking. This study aimed to develop a data-driven parsimonious triage algorithm for children under five years of age. Methods: This was a prospective observational study of children under-five years of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…However, there are very few studies that have used this emergency sign at triage. A prospective observational study by Mawji et al in Kenya 2018 found obstructed breathing was not statistically significant in children aged two to 60 months seeking treatment for an acute illness (46). Nevertheless, they recruited critically ill children below the age of five years unlike in this study where study participants were recruited every day and included critically ill children from one month to twelve years.…”
Section: Factors Associated With Dysglycemia Among the Study Particip...mentioning
confidence: 89%
“…However, there are very few studies that have used this emergency sign at triage. A prospective observational study by Mawji et al in Kenya 2018 found obstructed breathing was not statistically significant in children aged two to 60 months seeking treatment for an acute illness (46). Nevertheless, they recruited critically ill children below the age of five years unlike in this study where study participants were recruited every day and included critically ill children from one month to twelve years.…”
Section: Factors Associated With Dysglycemia Among the Study Particip...mentioning
confidence: 89%
“…The study nurse followed up on patients who were not admitted via telephone calls approximately two weeks after the hospital visit to determine if the patient recovered from the ailment without required admission later or in a different facility. More details about study procedures are described elsewhere ( Mawji et al , 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Features extracted using SSL were used to predict hospitalization using logistic regression. We also evaluated the utility of extracted features in improving logistic regression models trained using eight clinical features identified from previous analysis ( Mawji et al , 2021 ). The eight features include weight, restlessness, mid-upper arm circumference (MUAC), ability to drink/breastfeed, SpO 2 , temperature, difficulty breathing, and heart rate.…”
Section: Methodsmentioning
confidence: 99%
“…We compared end-to-end deep learning models initialized randomly with those initialized using weights learned by contrastive learning models. The models were trained on soft labels (label smoothing) recommended for noisy targets, and the minority class was oversampled to address class imbalance (Müller et al, 2019;Szegedy et al, 2015). We tuned hyperparameters for regularization (dropout, weight decay, data augmentation), batch size, learning rate, and label smoothing parameter using the ASHA algorithm.…”
Section: End-to-end Classification Using Deep Learningmentioning
confidence: 99%